Analisis Optimasi Hiperparameter Bayesian untuk Model Prediksi Kinerja Inovasi Berkelanjutan - Tika Puspita (University of Mataram, 2025)
This study examines how well the Gaussian Process Regression (GPR) model performs in interpreting the optimization outcomes achieved through Bayesian Optimization (BO) with Keras Tuner, specifically in the context of Sustainable Innovation Performance (SIP). The GPR surrogate model serves to examine the outcomes of optimization and offers valuable insights into the strategies of exploration and exploitation while seeking the most effective hyperparameters. The evaluation of the effectiveness of GPR involved calculating the Mean Absolute Error (MAE), which was bootstrapped 1000 times to establish a 95%. Confidence Interval (CI). This study's findings demonstrate the dependability of GPR in forecasting the validation loss generated by BO, characterized by minimal prediction errors and consistent confidence intervals. The results indicate that GPR serves as a dependable statistical method for assessing uncertainty in Bayesian-based optimization. Additionally, they offer valuable perspectives on how exploration and exploitation strategies can be utilized to attain optimal hyperparameter configurations. By strategically balancing exploitation and exploration, Bayesian Optimization can enhance the process of identifying optimal hyperparameter configurations within continuous innovation prediction models.